Identification of residues contributing to the ATP binding site of Kir6.2 - Trapp, Stefan (Oxford University Press, 2003)
The ATP-sensitive potassium (K(ATP)) channel links cell metabolism to membrane excitability. Intracellular ATP inhibits channel activity by binding to the Kir6.2 subunit of the channel, but the ATP binding site is unknown. Using cysteine-scanning mutagenesis and charged thiol-modifying reagents, we identified two amino acids in Kir6.2 that appear to interact directly with ATP: R50 in the N-terminus, and K185 in the C-terminus. The ATP sensitivity of the R50C and K185C mutant channels was increased by a positively charged thiol reagent (MTSEA), and was reduced by the negatively charged reagent MTSES. Comparison of the inhibitory effects of ATP, ADP and AMP after thiol modification suggests that K185 interacts primarily with the β-phosphate, and R50 with the γ-phosphate, of ATP. A molecular model of the C-terminus of Kir6.2 (based on the crystal structure of Kir3.1) was constructed and automated docking was used to identify residues interacting with ATP. These results support the idea that K185 interacts with the β-phosphate of ATP. Thus both N- and C-termini may contribute to the ATP binding site.